The risk of metabolic syndrome in patients with arterial hypertension in relation to psychological and biological risk factors - Nikolić, Gordana; Tasić, Ivan; Žikić, Olivera; Tošić Golubović, Suzana; Stojanović, Nikola; Simonović, Maja; Kostić, Jelena (Vojnosanitetski pregled, 2021)
Background/Aim. A type of personality and negative emotional reactions could be important for clustering biological risk factors for a cardiovascular disease in patients with arterial hypertension (AH). This study investigated if the patients with AH and psychological characteristics of the Distressed Type of personality with elevated anxiety/depression/aggression, have a higher risk of metabolic syndrome (MS) and explored value of the assessed parameters for MS occurrence. Methods.  A total of 85 patients with AH were included in the cross-sectional observational study. Type D Scale-14 (DS-14) was used to detect Type D (Distressed) personality. The Hospital Anxiety and Depression Scale (HADS) assessed the levels of anxiety and depression and the Buss Perry Aggression Questionnaire (BPAQ) was used for the assessment of aggression. The explored biological parameters included: blood pressure, lipid status, body mass index (BMI), the occurrence of diabetes mellitus (DM) and MS. Results. Type D patients were frequently more anxious, aggressive and had more frequent MS compared to non-type D. Type D females were younger, more anxious and had a greater prevalence of DM than those with non-type D personality. A multivariate analysis revealed that in type D personality patients with AH, depression had predictive value for MS. Conclusion. The occurrence of both MS and AH was in correlation with the type D personality, anxiety and depression. Early detection/treatment of depression in patients with AH and Type D personality could decrease a risk of metabolic syndrome.
Keywords: metabolic syndrome; hypertension; cardiovascular diseases; risk factors; personality; questionnaires; depression; comorbidity